A flexible wave-absorbing material for microelectronic field and a preparation method thereof

CN122941352APending Publication Date: 2026-10-20ANHUI MINGXUN NEW MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411609510.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0007]为了解决天然纤维织物复合吸波材料的耐久性差问题,本发明提供了一种用于微电子领域的柔性吸波材料的制备方法以及所得柔性吸波材料

Benefits of technology

[0021]有益效果:与现有技术相比,本发明通过在玄武岩纤维布上依次形成MXene层、钴链、氧化铝纳米阵列以及硅烷纳米膜,使得制备得到的吸波材料既具有天然纤维基材的柔软性,也获得了优异的吸波性能:MXene层和氧化铝阵列赋予了吸波材料高介电性能,钴链的存在进一步优化了吸波材料的电磁参数。此外,含氟苯基硅烷自组装膜的存在赋予了吸波材料优异的表面润滑性和防水性,有利于其在微电子结构中的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention provides a flexible microwave absorbing material for the microelectronics field and its preparation method. The method involves using basalt fiber cloth as a structural substrate, sequentially attaching an MXene layer, cobalt chains, and an alumina nanoarray. A thin film is then formed on the surface of the substrate through the hydrolysis and condensation of aminosilanes. Subsequently, the amino groups are replaced with fluorinated benzene rings via a cross-coupling reaction. The resulting structural microwave absorbing material exhibits excellent dielectric loss, magnetic loss, and resistive loss, as well as superior interfacial lubrication and water resistance, making it a promising candidate for application in the microelectronics field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of microwave absorbing materials technology, and particularly relates to a flexible microwave absorbing material for use in the field of microelectronics and its preparation method. Background Technology

[0002] With the rapid development of smart electronics and flexible wearable technologies, electromagnetic pollution is becoming increasingly serious. Electromagnetic waves not only harm human physical and mental health but also interfere with electromagnetic control systems, thus affecting the normal operation of precision equipment. Because electromagnetic wave absorbing materials (MAMs) dissipate electromagnetic waves through absorption without generating secondary pollution, they have been widely used in electromagnetic protection.

[0003] According to the loss mechanism of electromagnetic waves in materials, microwave absorbing materials can be divided into three categories: (1) When materials interact with electromagnetic waves, electromagnetic wave energy loss is mainly achieved through interface polarization, electronic polarization, and ion polarization. The more common dielectric loss type microwave absorbing materials mainly include SiC, ZnO and other materials. (2) When materials interact with electromagnetic waves, electromagnetic wave energy loss is mainly achieved through hysteresis loss, magnetic resonance, and eddy current loss. The more common magnetic loss type materials mainly include different ferrites and magnetic nanoparticles and their composite materials composed of metal elements such as iron, cobalt, and nickel. (3) Related to the conductivity of materials, electromagnetic wave energy loss is achieved through changes in macroscopic current caused by charge carriers. The more common resistive loss type microwave absorbing materials mainly include carbon materials, such as graphite, carbon nanotubes, and graphene, which have excellent thermal and chemical stability, good conductivity, low density, high temperature resistance and many other excellent properties. After years of accumulation and unremitting research, the research on microwave absorbing materials has made great progress and development. However, for practical applications, there is currently no material that can perfectly match the ideal performance requirements of thinness, wide absorption bandwidth, low reflection loss, and light weight of absorbing materials. Through a brief review of the research status of different types of absorbing materials, it can be seen that the future development of absorbing materials will move towards material composites, complementary performance, and multi-band compatibility. It is also likely to show an intelligent trend, that is, while having high-strength broadband absorbing performance, it can intelligently adjust itself according to changes in external conditions to meet the needs under different conditions.

[0004] However, traditional MAMs are large, rigid, and have limited functionality, making them unsuitable for foldable and smart wearable electronic devices. Therefore, the development of flexible MAMs is of great significance.

[0005] Currently, flexible microwave absorbing materials mainly include thin-film based microwave absorbing materials, fabric-based microwave absorbing materials, and aerogel-based microwave absorbing materials. Thin-film based microwave absorbing materials can be processed in two ways: blending and coating. Blending methods present challenges in the adhesion or dispersion of the absorbing agent in the flexible matrix, and the high penetration threshold of the absorbing component affects the absorption performance and the material's flexibility. Coating methods, on the other hand, suffer from issues related to coating strength and environmental resistance, such as corrosion resistance. Fabric-based microstructures (MAMs) have seen rapid development in recent years, especially with advancements in textile technology, leading to the rapid development of structural three-dimensional fabric microwave absorbing materials. However, the thickness of structural microwave absorbing fabrics severely limits their application in flexible wearable devices and next-generation flexible electronics. Traditional fabrics with two-dimensional planar structures, due to their controllable thickness and easily maintained flexibility, have great application potential in the field of flexible wearables.

[0006] Natural fiber fabric composite microwave absorbing materials have been extensively studied due to their environmental friendliness, flexibility, and lightweight characteristics. Because the fiber structure surface contains numerous active groups, which can form good bonds with microwave absorbing active materials through interactions such as hydrogen bonds, covalent bonds, or van der Waals forces, in-situ growth methods are often used to load the microwave absorbing active materials onto the substrate surface. However, composite microwave absorbing fabrics prepared by in-situ growth methods suffer from poor environmental adaptability and durability issues. Summary of the Invention

[0007] To address the poor durability of natural fiber fabric composite microwave absorbing materials, this invention provides a method for preparing flexible microwave absorbing materials for the microelectronics field, as well as the resulting flexible microwave absorbing material.

[0008] A method for preparing a flexible microwave absorbing material in the field of microelectronics includes the following steps: S1: An MXene layer is formed on the surface of the basalt fiber cloth; S2: Cobalt chains and aluminum oxide nanolayers are formed on the MXene layer; S3: Self-assembly of aminosilanes into a film on the surface of alumina nanolayers; S4: The amino groups on the surface are replaced with fluorinated benzene rings to obtain the flexible microwave absorbing material used in the microelectronics field.

[0009] In some embodiments of the present invention, the method for forming the MXene layer on the surface of the basalt fiber cloth includes the following steps: dissolving LiF in hydrochloric acid, then adding Ti3AlC2 powder to it, and stirring and reacting at a constant temperature of 35-45°C for 24 hours; repeatedly washing and centrifuging the obtained slurry until the pH of the supernatant is 6; ultrasonically treating the centrifuged product in an inert gas atmosphere for 1-2 hours and then centrifuging it again at 3500 rpm for 1 hour to obtain the MXene nanosheet concentrate; immersing the cleaned basalt fiber cloth in the obtained MXene nanosheet concentrate for 1-2 minutes, then taking it out and vacuum drying it to obtain the basalt fiber cloth containing the MXene layer.

[0010] Furthermore, the mixing ratio of LiF to hydrochloric acid is 1-2g: 20-25ml; the concentration of hydrochloric acid is 8-9mol / L.

[0011] Furthermore, the mass concentration of the MXene nanosheet concentrate is 1.5-2 mg / ml.

[0012] In some embodiments of the present invention, the cobalt chain formation method includes the following steps: dissolving cobalt chloride and sodium hydroxide in ethanol, stirring at room temperature for 1-2 hours to form a pink transparent liquid, adding 70-80 wt% hydrazine solution dropwise to it, and stirring again for 1-2 hours; heating the resulting mixture to 70-80°C and maintaining it for 1-2 hours until the reaction is complete, washing, filtering, and vacuum drying (80°C, 12 hours) of the resulting product to obtain the cobalt chain.

[0013] Furthermore, the mixing ratio of cobalt chloride, sodium hydroxide and ethanol is 0.005-0.009 mol: 0.06-0.08 mol: 100 ml.

[0014] In some embodiments of the present invention, the formation of the cobalt chains and alumina nanolayers on the surface of the MXene layer includes the following steps: SS1: Formation of alumina nanocrystal seed layer: Basalt fiber cloth containing MXene layer was immersed in 0.04-0.07 mol / L aluminum acetate ethanol solution for 10-15 min, and then dried at 200-220℃ for 30 min; the dried product was placed in 0.1-0.2 mol / L sodium hydroxide ethanol solution for 2-5 min, and then dried again for 30 min to obtain basalt fiber cloth containing alumina nanocrystals; SS2: Immerse the basalt fiber cloth obtained from SS1 into 150ml of deionized water containing 0.02-0.05g of cobalt chains, then take it out and dry it at 50-60℃ to form a basalt fiber cloth containing cobalt chains and alumina nanocrystals. SS3: The basalt fiber cloth obtained from SS2 is placed in a Teflon high-pressure reactor containing 0.05-0.08 mol / L aluminum nitrate solution and 0.05-0.06 mol / L hexamethylenetetramine solution. The mixture is heated to 65-75℃ and held for 2-3 hours. Then the temperature is increased to 90-105℃ and held for 10-12 hours. After cooling to room temperature, the product is filtered, washed, and dried to obtain the MXene layer with cobalt chains and alumina nanolayers.

[0015] When cobalt chains and alumina nanolayers are deposited on an MXene layer, a one-dimensional chain-like cobalt structure and a two-dimensional alumina nanoarray are obtained. The combination of these two structures creates numerous local heterogeneous interfaces on the MXene layer, exhibiting strong interfacial polarization, achieving good impedance matching and conductivity, and promoting the absorption of more electromagnetic waves. The periodic alumina array structure facilitates various reflections and scatterings, extending the propagation path of electromagnetic waves. The addition of cobalt chains further enhances interfacial polarization and achieves greater magnetic loss through natural resonance, exchange resonance, and eddy current resonance matrices.

[0016] However, highly concentrated cobalt chains can enhance the impedance mismatch between air and the thin film, resulting in more electromagnetic wave reflection and less absorption. Therefore, when attaching cobalt chains to the MXene layer, it is necessary to adjust the content of cobalt chains in the wetting solution used to control the proportion of cobalt chains in the final microwave absorbing material.

[0017] In some embodiments of the present invention, the formation of the aminosilane self-assembled film on the surface of the alumina nanolayer includes the following steps: using methanol as a solvent, an aminosilane solution with a volume fraction of 20-50% is prepared, and then basalt fiber cloth containing MXene layer, cobalt chain and alumina nanolayer is immersed in it for 24 hours, blown dry with high-purity nitrogen gas, and then dried to form the aminosilane self-assembled film.

[0018] In some embodiments of the present invention, the process of fluorinated benzene ring replacing amino groups includes the following steps: dissolving palladium catalyst, tetramethylethylenediamine and fluorobenzenetetramethyldioxoborane in dioxane, immersing basalt fiber cloth with an aminosilane self-assembled film in it, introducing an inert gas, heating at 110-130°C for 12-15 hours, and cooling to room temperature after the reaction is complete, followed by filtration, washing and drying.

[0019] In some embodiments of the present invention, the fluorobenzene tetramethyldioxoborane is specifically 2-(4-fluoro-2-isopropylphenyl)-4,4,5,5-tetramethyl-1,3,2-dioxoborane (CAS: 2098216-17-0), 2-(3-fluoro-2-isopropylphenyl)-4,4,5,5-tetramethyl-1,3,2-dioxoborane (CAS: 2098215-61-1), 1-(2-trifluoromethyl-4-methylphenyl)-4,4,5,5-tetramethyl-1,3,2-dioxoborane (CAS: 2223029-13-6), 2-(5-(difluoromethyl)-3-fluoro-2-methylphenyl)-4,4,5, At least one of 5-tetramethyl-1,3,2-dioxaborane (CAS: 2856022-19-8), 2-(2-(difluoromethoxy)-6-fluoro-4-methylphenyl)-4,4,5,5-tetramethyl-1,3,2-dioxaborane (CAS: 2913572-69-5), 2-(2,4-bis(difluoromethoxy)phenyl)-4,4,5,5-tetramethyl-1,3,2-dioxaborane (CAS: 2913572-73-1), and 2-(2-difluoromethoxy-4-trifluoromethoxyphenyl)-4,4,5,5-tetramethyl-1,3,2-dioxaborane (CAS: 2913572-68-4).

[0020] Since the flexible microwave absorbing material is used inside microelectronic devices, frictional loss is inevitable. Prolonged friction can lead to the loss of the core components in the flexible microwave absorbing material, resulting in a rapid loss of its excellent microwave absorption performance. To improve the lubricity of the surface of the flexible microwave absorbing material, this invention utilizes the hydrolysis and condensation reaction of aminosilanes to form an aminosilane self-assembled nanofilm. Furthermore, by utilizing the coupling reaction between amino groups and tetramethyldioxoborane containing fluorinated benzene rings, a fluorinated benzene ring is introduced into the self-assembled nanofilm, thereby improving the waterproof and stain-resistant properties of the flexible microwave absorbing material.

[0021] Beneficial Effects: Compared with existing technologies, this invention, by sequentially forming an MXene layer, cobalt chains, an alumina nanoarray, and a silane nanofilm on basalt fiber cloth, produces a microwave absorbing material that possesses both the flexibility of a natural fiber substrate and excellent microwave absorption performance. The MXene layer and alumina array impart high dielectric properties to the absorbing material, while the presence of the cobalt chains further optimizes its electromagnetic parameters. Furthermore, the presence of the fluorinated phenylsilane self-assembled film endows the absorbing material with excellent surface lubricity and water resistance, which is beneficial for its application in microelectronic structures. Detailed Implementation

[0022] The present invention will be described below with reference to specific embodiments. It should be noted that the following embodiments are examples of the present invention and are used only to illustrate the invention, not to limit it. Other combinations and various modifications within the scope of the present invention can be made without departing from its spirit or scope.

[0023] The following exemplarily illustrates the preparation of the cobalt chain used in the embodiments: 1.190 g (0.005 mol) of cobalt chloride hexahydrate and 2.4 g (0.06 mol) of sodium hydroxide were dissolved in 100 ml of ethanol and stirred at room temperature for 1 h to form a pink transparent liquid. 9 ml of 70 wt% hydrazine solution was added dropwise and stirred again for 1 h. The resulting mixture was heated to 70 °C and kept at that temperature for 1 h until the reaction was complete. The resulting product was washed, filtered, and vacuum dried to obtain the cobalt chain.

[0024] Example 1 S1: Forming an MXene layer on the surface of basalt fiber cloth: Dissolve 1g LiF in 20ml of 8mol / L hydrochloric acid, then add 2g Ti3AlC2 powder, and stir the mixture at a constant temperature of 35℃ for 24h; repeatedly wash and centrifuge the resulting slurry until the pH of the supernatant is 6; after ultrasonic treatment in a nitrogen atmosphere for 1h, centrifuge again at 3500rpm for 1h to obtain a concentrated MXene nanosheet solution (1.5mg / ml); immerse the cleaned basalt fiber cloth in the obtained concentrated MXene nanosheet solution for 1min, then remove and vacuum dry. Repeat this step three times to obtain a basalt fiber cloth containing an MXene layer; S2: Formation of cobalt chains and alumina nanoarrays on the MXene layer: Basalt fiber cloth containing the MXene layer was immersed in a 0.04 mol / L aluminum acetate ethanol solution for 10 min, and then dried at 200℃ for 30 min; the dried product was placed in a 0.1 mol / L sodium hydroxide ethanol solution for 2 min, and then dried again for 30 min to obtain basalt fiber cloth containing alumina nanocrystals; the obtained basalt fiber cloth containing alumina nanocrystals was immersed in a solution containing 0.02 g of cobalt chains. The product was placed in 150 ml of deionized water and then dried at 50 °C to form a basalt fiber cloth containing cobalt chains and alumina nanocrystals. The obtained basalt fiber cloth containing cobalt chains and alumina nanocrystals was placed in a Teflon high-pressure reactor containing 0.05 mol / L aluminum nitrate and 0.05 mol / L hexamethylenetetramine. The mixture was heated to 65 °C and held for 2 h, then heated to 90 °C and held for 10 h. After cooling to room temperature, the product was filtered, washed and dried to obtain an MXene layer with a cobalt chain and alumina nanoarray. S3: Self-assembly of aminosilane film on the surface of alumina nanoarray: A 20% (v / v) 3-aminopropyltrimethoxysilane solution was prepared using methanol as solvent. Basalt fiber cloth containing MXene layer, cobalt chain and alumina nanolayer was then immersed in the solution for 24 hours, dried with high-purity nitrogen, and dried at 90°C to form a self-assembled film. S4: Substitution of the fluorinated benzene ring on the surface amino group: Tetra(triphenylphosphine), tetramethylethylenediamine, and 2-(4-fluoro-2-isopropylphenyl)-4,4,5,5-tetramethyl-1,3,2-dioxoborane are dissolved in dioxane, such that the molar concentration of tetra(triphenyl)phosphine is 2 mol%, the molar concentration of tetramethylethylenediamine is 8 mol%, and the molar amount of 2-(4-fluoro-2-isopropylphenyl)-4,4,5,5-tetramethyl-1,3,2-dioxoborane is equal to the molar amount of aminosilane used; basalt fiber cloth with an aminosilane self-assembled film is immersed in it, nitrogen gas is introduced, and it is heated at 110°C for 15 h. After the reaction is completely cooled to room temperature, it is filtered, washed, and dried to obtain the flexible microwave absorbing material for the microelectronics field.

[0025] Example 2 S1: Forming an MXene layer on the surface of basalt fiber cloth: Dissolve 2g LiF in 25ml 9mol / L hydrochloric acid, then add 3g Ti3AlC2 powder, and stir the mixture at a constant temperature of 45℃ for 24h; repeatedly wash and centrifuge the resulting slurry until the pH of the supernatant is 6; after ultrasonic treatment in a nitrogen atmosphere for 2h, centrifuge again at 3500rpm for 1h to obtain a concentrated MXene nanosheet solution (2mg / ml); immerse the cleaned basalt fiber cloth in the obtained concentrated MXene nanosheet solution for 2min, then remove and vacuum dry. Repeat this step five times to obtain a basalt fiber cloth containing an MXene layer; S2: Formation of cobalt chains and alumina nanoarrays on the MXene layer: Basalt fiber cloth containing the MXene layer was immersed in a 0.06 mol / L aluminum acetate ethanol solution for 15 min, and then dried at 210℃ for 30 min; the dried product was placed in a 0.15 mol / L sodium hydroxide ethanol solution for 3 min, and then dried again for 30 min to obtain basalt fiber cloth containing alumina nanocrystals; the obtained basalt fiber cloth containing alumina nanocrystals was immersed in a solution containing 0.03 g of cobalt chains. The product was placed in 150 ml of deionized water and then dried at 60 °C to form a basalt fiber cloth containing cobalt chains and alumina nanocrystals. The obtained basalt fiber cloth containing cobalt chains and alumina nanocrystals was placed in a Teflon high-pressure reactor containing 0.07 mol / L aluminum nitrate and 0.06 mol / L hexamethylenetetramine. The mixture was heated to 75 °C and held for 3 h, then heated to 105 °C and held for 12 h. After cooling to room temperature, the product was filtered, washed and dried to obtain an MXene layer with a cobalt chain and alumina nanoarray. S3: Self-assembly of aminosilane film on the surface of alumina nanoarray: A 35% (v / v) 3-aminopropyltrimethoxysilane solution was prepared using methanol as solvent. Basalt fiber cloth containing MXene layer, cobalt chain and alumina nanolayer was then immersed in the solution for 24 hours, dried with high-purity nitrogen, and dried at 90°C to form a self-assembled film. S4: Substitution of the fluorinated benzene ring on the surface amino group: Tetra(triphenylphosphine), tetramethylethylenediamine, and 1-(2-trifluoromethyl-4-methylphenyl)-4,4,5,5-tetramethyl-1,3,2-dioxoborane are dissolved in dioxane, such that the molar concentration of tetra(triphenyl)phosphine is 2 mol%, the molar concentration of tetramethylethylenediamine is 8 mol%, and the molar amount of 1-(2-trifluoromethyl-4-methylphenyl)-4,4,5,5-tetramethyl-1,3,2-dioxoborane is equal to the molar amount of aminosilane used; basalt fiber cloth with an aminosilane self-assembled film is immersed in it, nitrogen gas is introduced, and it is heated at 120°C for 13 hours. After the reaction is completely cooled to room temperature, it is filtered, washed, and dried to obtain the flexible microwave absorbing material for the microelectronics field.

[0026] Example 3 S1: Forming an MXene layer on the surface of basalt fiber cloth: Dissolve 2g LiF in 25ml 9mol / L hydrochloric acid, then add 3g Ti3AlC2 powder, and stir the mixture at a constant temperature of 45℃ for 24h; repeatedly wash and centrifuge the resulting slurry until the pH of the supernatant is 6; after ultrasonic treatment in a nitrogen atmosphere for 2h, centrifuge again at 3500rpm for 1h to obtain a concentrated MXene nanosheet solution (2mg / ml); immerse the cleaned basalt fiber cloth in the obtained concentrated MXene nanosheet solution for 2min, then remove and vacuum dry. Repeat this step five times to obtain a basalt fiber cloth containing an MXene layer; S2: Formation of cobalt chains and alumina nanoarrays on the MXene layer: Basalt fiber cloth containing the MXene layer was immersed in a 0.07 mol / L aluminum acetate ethanol solution for 15 min, and then dried at 220℃ for 30 min; the dried product was placed in a 0.2 mol / L sodium hydroxide ethanol solution for 5 min, and then dried again for 30 min to obtain basalt fiber cloth containing alumina nanocrystals; the obtained basalt fiber cloth containing alumina nanocrystals was immersed in a solution containing 0.05 g of cobalt chains. The product was placed in 150 ml of deionized water and then dried at 60 °C to form a basalt fiber cloth containing cobalt chains and alumina nanocrystals. The obtained basalt fiber cloth containing cobalt chains and alumina nanocrystals was placed in a Teflon high-pressure reactor containing 0.08 mol / L aluminum nitrate and 0.06 mol / L hexamethylenetetramine. The mixture was heated to 75 °C and held for 3 h, then heated to 105 °C and held for 12 h. After cooling to room temperature, the product was filtered, washed and dried to obtain an MXene layer with a cobalt chain and alumina nanoarray. S3: Self-assembly of aminosilane film on the surface of alumina nanoarray: A 50% (v / v) 3-aminopropyltrimethoxysilane solution was prepared using methanol as solvent. Basalt fiber cloth containing MXene layer, cobalt chain and alumina nanolayer was then immersed in the solution for 24 hours, dried with high-purity nitrogen, and dried at 90°C to form a self-assembled film. S4: Substitution of the fluorinated benzene ring on the surface amino group: Tetra(triphenylphosphine), tetramethylethylenediamine, and 2-(2,4-bis(difluoromethoxy)phenyl)-4,4,5,5-tetramethyl-1,3,2-dioxoborane are dissolved in dioxane, such that the molar concentration of tetra(triphenyl)phosphine is 2 mol%, the molar concentration of tetramethylethylenediamine is 8 mol%, and the molar amount of 2-(2,4-bis(difluoromethoxy)phenyl)-4,4,5,5-tetramethyl-1,3,2-dioxoborane is equal to the molar amount of aminosilane used; basalt fiber cloth with an aminosilane self-assembled film is immersed in it, nitrogen gas is introduced, and it is heated at 120°C for 13 hours. After the reaction is completely cooled to room temperature, it is filtered, washed, and dried to obtain the flexible microwave absorbing material for the microelectronics field.

[0027] Example 4 Similar to Example 3, except that the mass of the cobalt chain used in S2 is 0.06g.

[0028] Comparative Example 1 Similar to Example 3, except that no cobalt chain is added.

[0029] Comparative Example 2 Similar to Example 3, except that no fluorophenylsilane self-assembled film is added.

[0030] Comparative Example 3 Similar to Example 3, except that tetramethyl fluorobenzene borane (2-(2,4-bis(difluoromethoxy)phenyl)-4,4,5,5-tetramethyl-1,3,2-dioxoborane) was not added.

[0031] Comparative Example 4 Similar to Example 3, except that fluorophenyltetramethylborane (2-(2,4-bis(difluoromethoxy)phenyl)-4,4,5,5-tetramethyl-1,3,2-dioxoborane) was replaced with 2-difluoromethyl-4,4,5,5-tetramethyl-1,3,2-dioxoborane (CAS: 2098256-49-4).

[0032] Performance testing Reflection loss: The flexible absorbing materials of each embodiment and comparative example were made into a ring with a thickness of 2 mm. The electromagnetic parameters (dielectric constant and permeability) were measured using an Agilent E5071C vector network analyzer. Then, the minimum reflection loss between 7-12 GHz was calculated and simulated. Friction coefficient: The friction coefficient of the absorbing material was measured at room temperature using an atomic force microscope. The probe sliding speed was 10 Hz, the load was 20 nN, and the scanning area was 2 μm × 2 μm. Water resistance: 13 μL of deionized water was dropped at 5 different locations on the absorbing material, and the contact angle between the material surface and the water was measured using a contact angle tester (Dataphysics OCA 25).

[0033] The test results are detailed in Table 1: Table 1 Performance test results of the microwave absorbing materials obtained in Examples 1-4 and Comparative Examples 1-4 As shown in Table 1, the flexible microwave absorbing material provided by this invention has a reflection loss of at least -32 dB, indicating that the material can achieve high-intensity absorption of electromagnetic waves. Furthermore, the microwave absorbing material also exhibits excellent surface lubricity and water resistance. The results of Comparative Examples 2-3 show that the presence or absence of the fluorobenzene silane self-assembled film not only affects the surface lubricity and water resistance of the microwave absorbing material but also its microwave absorption performance. This may be because the uneven electron distribution on the benzene ring leads to charge accumulation at the interface, thereby affecting the interfacial polarization of the microwave absorbing material.

[0034] In summary, the flexible microwave absorbing material provided by this invention shows promising application prospects in microelectronic structures.

Claims

1. A method for preparing a flexible microwave absorbing material for use in the field of microelectronics, characterized in that, Includes the following steps: S1: An MXene layer is formed on the surface of the basalt fiber cloth; S2: Cobalt chains and alumina nanoarrays are formed on the MXene layer; S3: Self-assembly of aminosilanes into a film on the surface of alumina nanolayers; S4: The amino groups on the surface are replaced with fluorinated benzene rings to obtain the flexible microwave absorbing material used in the microelectronics field.

2. The method for preparing flexible microwave absorbing material for the microelectronics field according to claim 1, characterized in that, The method for forming the MXene layer on the surface of the basalt fiber cloth includes the following steps: dissolving LiF in hydrochloric acid, then adding Ti3AlC2 powder to it, and stirring and reacting at a constant temperature of 35-45℃ for 24h; repeatedly washing and centrifuging the obtained slurry until the pH of the supernatant is 6; ultrasonically treating the centrifuged product in an inert gas atmosphere for 1-2h, and then centrifuging it again at 3500rpm for 1h to obtain the MXene nanosheet concentrate; immersing the cleaned basalt fiber cloth in the obtained MXene nanosheet concentrate for 1-2min, and then taking it out and vacuum drying it. This step is repeated no more than 5 times to obtain the basalt fiber cloth containing the MXene layer.

3. The method for preparing flexible microwave absorbing material for the microelectronics field according to claim 2, characterized in that, The mixing ratio of LiF to hydrochloric acid is 1-2g: 20-25ml; the concentration of hydrochloric acid is 8-9mol / L.

4. The method for preparing flexible microwave absorbing material for the microelectronics field according to claim 2, characterized in that, The mass concentration of the MXene nanosheet concentrate is 1.5-2 mg / ml.

5. The method for preparing flexible microwave absorbing material for the microelectronics field according to claim 2, characterized in that, The preparation method of the cobalt chain includes the following steps: dissolving cobalt chloride hexahydrate and sodium hydroxide in ethanol, stirring at room temperature for 1-2 hours to form a pink transparent liquid, adding 70-80 wt% hydrazine solution dropwise, and stirring again for 1-2 hours; heating the resulting mixture to 70-80℃ and maintaining it for 1-2 hours until the reaction is complete, washing, filtering, and vacuum drying the resulting product to obtain the cobalt chain.

6. The method for preparing flexible microwave absorbing material for the microelectronics field according to claim 5, characterized in that, The mixing ratio of cobalt chloride, sodium hydroxide and ethanol is 0.005-0.009 mol: 0.06-0.08 mol: 100 ml.

7. The method for preparing flexible microwave absorbing material for the microelectronics field according to claim 2, characterized in that, The formation of the cobalt chains and alumina nanoarrays on the surface of the MXene layer includes the following steps: SS1: Formation of alumina nanocrystal seed layer: Basalt fiber cloth containing MXene layer was immersed in 0.04-0.07 mol / L aluminum acetate ethanol solution for 10-15 min, and then dried at 200-220℃ for 30 min; the dried product was placed in 0.1-0.2 mol / L sodium hydroxide ethanol solution for 2-5 min, and then dried again for 30 min to obtain basalt fiber cloth containing alumina nanocrystals; SS2: Immerse the basalt fiber cloth obtained from SS1 into 150ml of deionized water containing 0.02-0.05g of cobalt chains, then take it out and dry it at 50-60℃ to form a basalt fiber cloth containing cobalt chains and alumina nanocrystals. SS3: The basalt fiber cloth obtained from SS2 is placed in a Teflon high-pressure reactor containing 0.05-0.08 mol / L aluminum nitrate and 0.05-0.06 mol / L hexamethylenetetramine. The mixture is heated to 65-75℃ and held for 2-3 hours. Then, the temperature is increased to 90-105℃ and held for 10-12 hours. After cooling to room temperature, the product is filtered, washed, and dried to obtain an MXene layer with cobalt chains and alumina nanoarrays.

8. The method for preparing flexible microwave absorbing material for the microelectronics field according to claim 1, characterized in that, The formation of the aminosilane self-assembled film includes the following steps: using methanol as a solvent, an aminosilane solution with a volume fraction of 20-50% is prepared, and then basalt fiber cloth containing MXene layer, cobalt chain and alumina nanolayer is immersed in it for 24 hours, blown dry with high-purity nitrogen gas, and then dried to form an aminosilane self-assembled film.

9. The method for preparing flexible microwave absorbing material for the microelectronics field according to claim 1, characterized in that, The process of replacing amino groups with fluorinated benzene rings includes the following steps: dissolving 2-3 mol% palladium catalyst and fluorobenzene tetramethyl dioxane in dioxane, immersing basalt fiber cloth with an aminosilane self-assembled film in it, introducing inert gas, heating at 110-130℃ for 12-15 h, and cooling to room temperature after the reaction is completely cooled, followed by filtration, washing, and drying.

10. The flexible absorbing material prepared by the method for preparing flexible absorbing material for the microelectronics field according to any one of claims 1-9.